Desenvolvimento de modelo matemático para determinação da velocidade de chama laminar de hidrocarbonetos gasosos e hidrogênio - Eduardo Abreu Salomão (2021)
Recent forecasts indicate a strong trend in the industry to change its energy matrix to sustainable energy sources, migrating from dependence on burning heavy hydrocarbons and coal, to lighter hydrocarbons and, in the future, to hydrogen and other renewable fuels. Aiming to accelerate this migration, governments and the private sector have invested in research in the area to ensure reliability and high efficiency of processes and equipment in this new scenario. One of the shortest routes evaluated has been the adequacy of existing equipment in operation to work with different fuels, making them multi-fuel, preserving efficiency, operating range, and strict control of polluting gas emissions. This requires a deep understanding of the dynamics and nature of combustion, the properties of fuels, and the flow regime in which these equipments operate. In the present work, a simplified global reaction model is elaborated, capable of estimating the laminar flame velocity of the short-chain hydrocarbons and hydrogen. The model is designed to meet a wide range of conditions, including reactants preheating and oxy-combustion. The model is evaluated against experimental data collected by several authors under different conditions and results calculated by detailed models available in the literature. The laminar propagation speed of each chemical species is displayed and compared to reference values under various operating conditions. The results demonstrate good consistency between the values chosen by the model and those reported in the literature. Bench tests are performed to estimate the laminar propagation velocity of LPG. A model for the treatment of turbulent flame velocity is proposed and evaluated against the expected results. The results obtained are close to the theoretical model developed. The constants obtained for the simplified global model, as well as the source code developed, are available for calculating the laminar flame velocity in a wide range of scenarios, with a high degree of accuracy.